Strategi Pemasaran Industri Kreatif Berbasis Kearifan Lokal Di Masa Pandemi Covid-19 (Studi Pada Batik Desa Sidomulyo Kabupaten Jember) - Noga Riza Faisol (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
The marketing mix is ​​a combination of four variables which are the core of the marketing system that can be controlled by the company. These variables can be grouped into four main groups known as the 4Ps, namely: Product (product), Price (price), Promotion (promotion), Place (Place / Distribution). The focus of research in this journal is 1). What is the marketing strategy of Batik in Sidomulyo Village, Jember Regency during the COVID-19 pandemic. 2). What are the obstacles faced by Batik in Sidomulyo Village, Jember Regency during the COVID-19 pandemic? 3). What are the solutions to the problems faced by Batik SMEs in Sidomulyo Village, Jember Regency during the COVID-19 pandemic? This study uses a descriptive qualitative approach, the type of research uses field research, data collection techniques use observation, interviews and documentation. Data analysis used descriptive qualitative analysis with the stages of data reduction, data presentation and conclusions. The validity of the data was tested by using source triangulation techniques and techniques or methods. The results of the study concluded that: The marketing strategy of Batik in Sidomulyo Village, Jember Regency uses market segmentation analysis by looking at the way consumers dress and the way consumers speak, and uses a marketing mix marketing mix including: Product strategy, Batik in Sidomulyo Village maintains good product quality from the coloring process , embedding, and motifs for the quality of the fabric depending on consumer demand. And the resulting product is a durable product.